+0  
 
+1
249
2
avatar

how would i do this?    2x+3=53x-1

Guest May 4, 2017
 #1
avatar+87629 
+2

 

2^(x + 3)  = 5^(3x - 1)  take the log of both sides

 

log 2^(x + 3)  = log 5^(3x - 1)    and we can write

 

(x + 3) log 2  = (3x - 1) log 5     simplify

 

x log 2 + 3 log 2  =  3x log 5 - log 5     rearrange as

 

x log 2 - 3x log 5   =  - 3 log 2 - log 5     multiply through by -1

 

3x log 5 - x log 2  =  3log 2 + log 5   factor the left side

 

x (3 log 5 - log 2)  = 3log 2 + log 5      divide both sides by (3 log 5 - log 2 )

 

x  =  [ 3log 2 + log 5 ] / [ 3 log 5- log 2 ]  ≈   .892

 

 

cool cool cool

CPhill  May 4, 2017
 #2
avatar
+1

Thank You!!!

Guest May 4, 2017

12 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.